Penerapan Web-Based Homecare Management System Dengan Fitur Reservasi Dan Konsultasi Virtual Untuk Meningkatkan Efisiensi Layanan Kesehatan Homecare - Aktavia, Widodo; Nilovar Asyiah (Jurnal Ilmu Komputer, 2026)
Homecare services have become an important solution in providing health care at home, especially for patients who need long-term care or cannot access health facilities directly, such as the elderly, post-natal mothers and babies. However, challenges in schedule management and service efficiency often become obstacles in homecare service operations. This research aims to develop and implement a web-based homecare information system with a reservation feature to increase the efficiency of health services. The case study was conducted on Yunia Khomsati A.Md Keb., SKM., M.K.M, a public health master's graduate collaborating with her friend, the same graduate and her 2 nursing assistants who wanted to help the people around her who needed care at home. This system is designed to facilitate the process of homecare service facilities, managing schedules, home addresses of homecare providers, communication between patients and service providers if they want to be served at the patient's home. The implementation of this system will be able to expand information that it turns out that patients who need care services can do so at home, can make online reservations and know the rates for services provided by nurses. There are 2 types of services available in this homecare service, namely coming to the practice's home or a nurse coming to the patient's house. It is hoped that this research can find effective and practical solutions to increase the efficiency of technology-based homecare services.